“The Forest Has Become Our New Living Room” – The Critical Importance of Urban Forests During the COVID-19 Pandemic - Weinbrenner, Hannes; Breithut, Jasmin; Hebermehl, Wiebke; Kaufmann, Anna; Klinger, Tabea; Palm, Therese; Wirth, Kristina (Frontiers in Forests and Global Change, 2021)
Out of nowhere the COVID-19 pandemic has turned people's everyday lives upside down. Public places in urban areas were closed. However, leaving the house for recreational and leisure purposes in nature was still allowed in Germany – even during lockdown in March and April. As a result, urban forests have gained unprecedented importance - not only for recreational activities, but also for maintaining social contacts and coping with psychological stress. With these diverse requirements, many people have appropriated urban forests in new and changed ways. Using the example of the forests around the southern German city of Freiburg, a team of researchers from the Department of Societal Change at the Forest Research Institute Baden-Württemberg (FVA) carried out a mixed-method study to investigate how these appropriation practices are working and to shed some light on the relevance of forests for city residents in these circumstances. In addition to the statistical analysis of an online questionnaire, ethnographic observation data and Instagram posts were analyzed. This methodological triangulation was carried out in order to purposefully combine the strengths of each method while at the same time reducing the intrinsic biases and blind spots. This resulted in a better understanding of the importance of urban forest during this extraordinary period of time. Our results show that urban forests became critically important during the lockdown. Many visitors appropriated the forest with very different motives and for different purposes. For many visitors, the forest provided the same functions during this extraordinary period that public spaces otherwise do. The forest was not only consumed as a natural space, but also constructed by visitors as a social space. We can illustrate how this social meaning was both negotiated and reproduced. To provide an abstraction of our results, we refer to the theory of spatial appropriation as well as to new spatial sociological approaches that conceptualize space as a network of social relations. These results give rise to broader questions for future research projects, recreational forest research, forest and health, and forest planning.